INVESTIGATION OF FACTORS AFFECTING CORE COMPRESSIVE STRENGTH AND NON-DESTRUCTIVE TESTING OF CONCRETE - Kabay, Nihat; Akoz, Fevziye (YILDIZ TECHNICAL UNIV, 2020)
This paper investigates several factors such as the effect of drilling, moisture content and presence of reinforcement on the compressive strength of core samples and the effect of reinforcement and concrete age on the rebound number and ultrasonic pulse velocity of concrete. Test results show that the effect of moisture on core strength was lower than the other factors. Due to the drilling effect, the core compressive strength was reduced by 11%. The presence and the number of reinforcement in core samples significantly affected the compressive strength. On average, the reduction in strength of cores that contain single and two bars was found as 12% and 16% respectively. The rebound number and ultrasonic pulse velocity values increased with the age of concrete. The reinforcement did not have a significant effect on the non-destructive test results. However, direct and indirect ultrasonic pulse velocity results differed significantly and on average this ratio was found to be 1.16 and 1.17 for plain and reinforced concrete members, respectively.
Keywords: Core correction factors; compressive strength; non-destructive testing; DIAMETER; LENGTH; Engineering